Effect of Refining Intensity on Pulp and Paper Properties Made of Eucalyptus Camaldulensis Wood - Behzad Kord (Regional Information Center for Science and Technology (RICeST), 2009)
This study is for identifying of  the effect of refining intensity on pulp and paper properties made from eucalyptuswood. For this purpose three normal eucalyptus camaldulensis spp trees were randomly cut down from Shastkolateh Experimental Forest located in Gorgan. From each tree, one disk with 50cm thickness from breast height were selected for pulp making. Then disks converted to chips by chipper, and the chips were cooked by kraft process, the cooking conditions were as following effective alkali 20%, sulfidity 25%, tempreture 190 0C and Time 90min. After cooking and pulping process, the pulp refined with PFI Mill in 5 different intensity with 0 rpm, 500 rpm, 1500 rpm, 2500 rpm and 3500 revelutions. Then, papermaking and measuring the paper properties such as freeness, tensile strength, tear strength, burst strength and density were done. Then data were statisticaly analysed. The results indicated that, there are significant difference between pulp and paper properties made of eucalyptus camaldulensis spp wood with 5 different refining  intensity in 95% confident level. As increasing of refining intensity and refining revolutions, freeness and tear strength of paper decreased but  tensile strength, burst strength and density of paper incrased. However, the highest value of freeness and tear strength of paper related to refining intensity with 0rpm revelution (without refining) and highest value of tensile strength, burst strength and density of paper related to  refining intensity with 3500rpm revelution